Hubungan Kepatuhan Minum Obat dengan Kualitas Hidup Pasien Tuberkulosis Paru di Ruang Rawat Inap RS Bhayangkara Medan Tahun 2025 - Susanti, Nofi; Tiana, Triswa (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Tuberculosis (TB) is an infectious disease that remains a public health problem worldwide, including in Indonesia. This disease is caused by the bacterium Mycobacterium tuberculosis. The aim of this study was to determine the relationship between medication adherence and quality of life in inpatients with pulmonary tuberculosis (TB) at Bhayangkara Hospital in Medan. Methods: This study used a cross-sectional approach with a sample of 30 diagnosed pulmonary TB patients receiving anti-TB treatment. Data were collected through medical records and questionnaires, and analyzed using the chi-square test with a significance level of 0.05. Results: The results showed a significant relationship between medication adherence and improved patient quality of life (p=0.032). Adherent patients tended to have a better quality of life compared to non-adherent patients. Conclusion: TB medication adherence is crucial in achieving recovery and improving patient quality of life, as well as preventing drug resistance.